2371. Monomicrobial Gram-Negative Necrotizing Fasciitis: An Uncommon but Fatal Syndrome. (26th November 2018) - Park, Se Yoon; Yu, Shi Nae; Lee, Eun Jung; Kim, Tark; Jeon, Min Hyok; Choo, Eun Ju; Park, Suyeon; Bang, Hae In; Han, Jaijun; Park, Jebyung; Kim, Tae Hyong
Abstract: Background: Necrotizing fasciitis is a rapid progressive and potentially life-threatening infection. Although the relative emergence of non-synergistic single Gram-negative organisms as pathogen could be a therapeutic issue for clinicians, limited studies so far described the characteristics due to the low incidence. Methods: We retrospectively reviewed clinical data of necrotizing fasciitis patients who were clinically diagnosed between May 2001 and December 2015 in university hospitals of three different cities of the Republic of Korea. We compared clinical characteristics and outcomes of patients with monomicrobial Gram-negative with those of the Gram-positive counterpart. Results: A total of 115 patients with community acquired necrotizing fasciitis were identified. Among them, monomicrobial infections were 67 (58%) cases: 31 (27%) in the Gram-negative group and 36 (31%) in the Gram-positive group. The majority of Gram-negative group was E. coli followed by K. pneumonia and V. vulnificus . There were more cases of the Gram-negative group showing liver cirrhosis (39% vs. 14%, P = 0.02) and bacteremia (52% vs. 16%, P = 0.02). A total of 23 (10%) patients died within 30 days, including 15 (19%) in the Gram-negative group and 8 (10%) in the Gram-positive group ( P = 0.02). In multivariable logistic regression, liver cirrhosis (adjusted odds ratio [aOR], 13.7; 95% confidence interval [CI], 2.9–67.0), treatment with antibiotics without surgery (aOR, 10.2; 95% CI, 2.1–48.3), and lower level of albumin (aOR 4.9; 95% CI, 1.6–14.9) were significantly associated with 30-day mortality. Conclusion: Our findings suggest that necrotizing fasciitis caused by Gram-negative pathogen more often associated with liver cirrhosis and has poorer outcomes than the Gram-positive counterpart. Disclosures: All authors: No reported disclosures.